Design and Testing of In-store Paddy Drying - Somkiat Prachayawarakorn; Somchart Soponronnarit; Prasai Chalidapongs; Adisak Nathakaranakule (Agriculture and Natural Resources, 1994)
The objective of this paper was to design and test of in-store pady drying. Both energy consumption and grain quality were taken into consideration. Economic analysis was also conducted. Experimental results indicated that uniform air flow through paddy bed was achieved. Pressure drop through the grain bed was the most significant. When paddy was dried from 16% to about 14% wet-basis, using an air flow rate of 2.03 m3/min-m3 of paddy, energy consumption was 19 bath/ton, head yield was 11% higher conpared with direct sun drying. Benefit gained from higher head yield was 160 baht/ton. Dry paddy in storage should be ventilated periodically by ambient air, at least one hour each time. Mathematical simulation of paddy drying indicated that energy consumption was 35 baht/ton when paddy was dried from 18% to 14% wet-basis, using an air flow rate of 1.3 m3/min-m3 of paddy. Economic analysis based on mathematical model data showed that in-store drying system yielded higher rate of return compared with interest rate and short pay back period.